Protection of Economic Competition and Intellectual Property: Search for an Optimal Regulatory Model - Us, M.V.; Titko, I.A. (Science and Innovation, 2024)
Introduction. Failure to comply with the rules of competition is often associated with breach of intellectual property rights of other parties or misuse of these rights by authorized entities themselves. Problem Statement. The foregoing implies a whole set of problems related to ensuring the protection of economic competition and intellectual property rights, as well as to preventing the abuse of these rights, which often leads to restrictions of competition. Purpose. To study regulations and legislative acts concerning the protection of economic competition and intellectual property both at the national and international levels, the interaction and coherence of competition law and regulations in the field of rights to intellectual labor results. Materials and Methods. The research is based on the legislation of Ukraine and international legal acts, as well as the practice of the national courts of Ukraine, the Court of Justice of the European Union, and the administrative practice of the European Commission. The methodological framework of the research comprises the methods for historical, dialectical, systematic, and logical research, the formal legal method, and the method of comparative jurisprudence. Results. The relationship between the competition law and the intellectual property law has been established, the consequences of the imbalance between them (creation of monopolies, fragmentation of the internal market, market stagnation) have been identified, ways to avoid these negative consequences have been suggested. Conclusions. The regulations and laws in the field of protection of economic competition and the exercise of intellectual property rights should be based on a model according to which the competitive behavior implies the observance of intellectual property rights of other parties, with the behavior of right owners leading to neither any restriction of competition nor any breach of consumer rights.